Description of Metarhabditis giennensis sp. n. (Nematoda, Rhabditida, Rhabditidae) from decaying wood of a riverbank forest in the southern Iberian Peninsula - Abolafia, Joaquín; Peña-Santiago, Reyes (Zootaxa, 2019)
A new species of the genus Metarhabditis, M. giennensis sp. n., collected from a riverbank poplar forest in the southern Iberian Peninsula, is described and illustrated, including SEM observations. The new species is characterized by its 1.01–1.16 mm long body in females and 0.77–0.98 in males, cuticle with very fine transverse striation, lip region 9–14 µm broad and consisting of six swollen rounded lips fused in pairs, stoma 14–25 µm long with tubular gymno-promesostegostom, pharynx with slightly swollen metacorpus and slender isthmus, nerve ring, excretory pore and deirids located at isthmus level, female reproductive system didelphic-amphidelphic, vulva equatorial (V = 49–50), female rectum length 1.2–1.7 times the anal body width, female tail conical-elongate with acute tip (123–199 µm, c = 5.8–8.2, c’ = 8.2–11.1), male tail conical (34–56 µm, c = 15.5–25.7, c’ = 2.4–3.5), bursa leptoderan, 32–41 µm long spicules with rounded and ventrally bent manubrium, and 17–20 µm long gubernaculum. An updated list of species of the genus and a key for their identification are also provided. [Zoobank URL: urn:lsid:zoobank.org:act:7EBAC9DB-A148-4A1A-97E5-3B796D0839BF]